2023
DOI: 10.1101/2023.10.04.560903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harnessing Landrace Diversity Empowers Wheat Breeding for Climate Resilience

Shifeng Cheng,
Cong Feng,
Luzie U. Wingen
et al.

Abstract: Breeding crops resilient to climate change is urgently needed to help ensure food security. A key challenge is to harness genetic diversity to optimise adaptation, yield, stress resilience and nutrition. We examined the genetic and phenotypic diversity of the A.E. Watkins landrace collection of bread wheat (Triticum aestivum), a major global cereal, through whole-genome re-sequencing (827 Watkins landraces and 208 modern cultivars) and in-depth field evaluation spanning a decade. We discovered that modern cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…S3F and G). A larger proportion of SNPs were significantly associated with starch and protein content in a previously characterized wheat population (Cheng et al, 2023), compared to other genomic regions (Fig. 3K and fig.…”
Section: Resultsmentioning
confidence: 86%
“…S3F and G). A larger proportion of SNPs were significantly associated with starch and protein content in a previously characterized wheat population (Cheng et al, 2023), compared to other genomic regions (Fig. 3K and fig.…”
Section: Resultsmentioning
confidence: 86%
“…Such focussed selection of samples coupled with the tendency to used sequence capture prior to sequencing could lead to the exclusion of rare alleles and a strong ascertainment bias (You et al ., 2018). Recent large scale skim sequencing (Cheng et al . 2023) of a highly diverse set of globally significant breeding and landrace accessions made available a new source of SNPs free of ascertainment bias and suitable for global users.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP calls generated from skim sequence data from 315 wheat accessions (204 elite wheat lines and 111 wheat landraces taken from the Watkins "Core Collection" -Supplementary File S1) were used as the source of SNPs for haplotype optimisation (Cheng et al 2023). Varieties with >= 1% heterozygous loci were excluded.…”
Section: Marker Selection: Skim Sequence Sourced Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplotype analysis was run across the genomic sequence of the AVR-Rmg8 resistance interval in the full Watkins collection (827 accessions) and a selection of modern wheat varieties (218 cultivars) using SY-Mattis as the reference genome 14,19 . A cluster heat map with 50 kb window size was generated to identify regions identical or near-identical to SY-Mattis which revealed that an additional 20 accessions of the Watkins collection carry sections of the 5.3 Mbp interval.…”
Section: Interrogating the 53 Mbp Chromosome 2a Intervalmentioning
confidence: 99%